Obligation to Pay Telecommunications Operation Rights Fees and Contribution of Universal Service Obligations for The Palapa Ring Project by The Palapa Ring Project Implementing Business Entity - Darien Aldiano; Dian Puji Nugraha Simatupang (LEGAL BRIEF, 2022)
Cooperation between the Government and Business Entities on Infrastructure Provision (PPP) in this case of the Palapa Ring is a project of greater concern to the Government of Indonesia, because its not only has benefits for internet distribution that reaches all areas in Indonesia, but it has a large income impact on the state budget and eases the burden of state budget funds, this is because of the payment scheme in the PPP. Therefore, the obligation to pay the Telecommunications Operation Rights Fee (BHP TEL) and the Universal Service Obligation Contribution (USO) by the Business Entity is very important. The methodology in this article is descriptive normative, with the purpose of writing to focus on knowing the payment obligations of BHP and USO with the type of business activity, and to find out the procedures for calculating BHP and USO based on regulations. The conclusion of this paper First, based on the Minister ICT Regulation, Business Entities that have obtained a license to operate a telecommunications network have an obligation to pay BHP and USO, this is because as a form of compensation for the licenses obtained in network operation by ministry. Second, minister ICT Regulation stipulates that in calculating BHP and USO, it is inseparable from AP payments, this is because the source of AP funds is from USO payments. The authors recommend to separate for the portion of Capital Expenditure (capex) and AP for Operating Expenditure (opex), to calculate BHP Tel and USO contributions.